Feature-Trace : an approach to generate operational profile and to support regression testing from BDD features - Barbosa, Rafael Fazzolino Pinto (2020)
Dissertação (mestrado)—Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, 2020.